The impact of social, economic and health factors on the employment of the elderly in the center of Amara district - Wisam A. Dargal ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
Al-Amarah District Center is considered to be one of the Iraqi districts where the phenomenon of elderly labor is widespread. The serious phenomenon has unsatisfactory consequences at both the family and societal levels. It is distributed in varying numbers depending on the type of work performed by the elderly within the neighborhood of the study.The research aims to identify the demographic, residential, and educational characteristics of the elderly sample that led to their entry into labor market. The findings indicate that 68% live in rented or informal (encroached) housing, 92% fall within the age group of 65-74 years, and 72% have an educational level of primary school or below. The study also examined the economic impacts, represented by wages insufficient to meet family needs (90%); the social impacts, with 84% frequently visiting cafes, smoking, and engaging in quarrels; and the health impacts, as 42% are exposed to bruises and fractures resulting from their work.The research relied on a sample of 50 elderly individuals, equally distributed between males and females, aged 65 years and above. Data were collected through responses to a questionnaire addressing the phenomenon of elderly labor. Accordingly, recommendations were developed based on the study’s conclusions to help reduce this phenomenon.DOI: https://doi.org/10.54633/2333-025-058-001